Pengaruh Rasio Hutang, Profit Margin Dan Ukuran Perusahaan Terhadap Financial Distress - Norisa Putri; Erly Mulyani (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to examine the effect of debt ratio, profit margins, and firm size on financial distress. This research is classified as causative research. The population in this study is the main sector companies listed on the Indonesia Stock Exchange in 2013-2017. The sample collection technique in this study used a purposive sampling method, then 25 companies were obtained as a research sample. Financial distress variable is measured using the Zmijewsky Score model, debt ratio variable is measured by debt to total assets, profit margin variable is measured by net profit margin and firm size variable is measured by log of total assets. The type of data used is secondary data obtained from www.idx.co.id. The analytical method used is panel regression analysis. The empirical results of this study indicate that the debt ratio has a positive and significant effect on financial distress, profit margins have a negative and significant effect on financial distress, and firm size has a negative and significant effect on financial distress